Considerations in the choice of a skin donor site for harvesting keratinocytes containing a high proportion of stem cells for culture in vitro - Lavoie, Amélie; Fugère, Claudia; Fradette, Julie; Larouche, Danielle; Paquet, Claudie; Beauparlant, Annie; Gauvin, Robert; Têtu, Félix-André; Roy, Alphonse; Bouchard, Maurice; Genest, Hervé; Auger, François A.; et al. (Burns, 2011)
The treatment of severely burned patients has benefited from the grafting of skin substitutes obtained by expansion of epithelial cells in culture. The aim of this study was to evaluate whether the anatomic site chosen for harvesting skin had an impact on the quality of the derived cell cultures. Considering that hair follicles contain epithelial stem cells, we compared hairy skin sites featuring different densities and sizes of hair follicles for their capacity to generate high quality keratinocyte cultures. Three anatomic sites from adult subjects were compared: scalp, chest skin and p-auricular (comprising pre-auricular and post-auricular) skin. Keratin (K) 19 was used as a marker to evaluate the proportion of stem cells. Keratinocytes were isolated using the two-step thermolysin and trypsin cell extraction method, and cultured in vitro. The proportion of K19-positive cells harvested from p-auricular skin was about twice that of the scalp. This K19-positive cell content also remained higher during the first subcultures. In contrast to these in vitro results, the number of K19-positive cells estimated in situ on skin sections was about double in scalp as in p-auricular skin. Chest skin had the lowest number of K19-positive cells. These results indicate that in addition to the choice of an adult anatomic site featuring a high number of stem cells in situ, the quality of the cultures greatly depends on the ability to extract stem cells from the skin biopsy.